2020
DOI: 10.1093/braincomms/fcaa112
|View full text |Cite
|
Sign up to set email alerts
|

Restoring regulatory T-cell dysfunction in Alzheimer’s disease through ex vivo expansion

Abstract: Inflammation is a significant component of Alzheimer disease pathology. While neuroprotective microglia are important for containment/clearance of Amyloid plaques and maintaining neuronal survival, Alzheimer inflammatory microglia may play a detrimental role by eliciting tau pathogenesis and accelerating neurotoxicity. Regulatory T cells have been shown to suppress microglia-mediated inflammation. However, the role of regulatory T cells in ameliorating the proinflammatory immune response in Alzheimer disease r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 91 publications
2
53
0
Order By: Relevance
“… 49 , 72 74 Tregs are found to be decreased and/or dysfunctional in a number of diseases such as systemic lupus erythematosus, type 1 diabetes, multiple sclerosis, amyotrophic lateral sclerosis, and Alzheimer’s disease. 49 , 50 , 72 , 75 82 The current study demonstrates decreased numbers of Tregs in patients with PD. More importantly, this study demonstrates impaired Treg suppressive function starting early in disease and worsening as disease progresses.…”
Section: Discussionsupporting
confidence: 51%
“… 49 , 72 74 Tregs are found to be decreased and/or dysfunctional in a number of diseases such as systemic lupus erythematosus, type 1 diabetes, multiple sclerosis, amyotrophic lateral sclerosis, and Alzheimer’s disease. 49 , 50 , 72 , 75 82 The current study demonstrates decreased numbers of Tregs in patients with PD. More importantly, this study demonstrates impaired Treg suppressive function starting early in disease and worsening as disease progresses.…”
Section: Discussionsupporting
confidence: 51%
“…Another strategy that might be useful to explore would be the reconstitution of Treg cells in AD patients. It has recently been shown that Treg anti-inflammatory function is impaired in patients with AD, but had increased suppressive activity on effector T cell proliferation and macrophage activation following ex vivo clonal expansion (140). This suggests that Treg function and immunophenotype are impaired in AD, but that administration of ex vivo clonally expanded of Tregs might be a viable therapeutic option (140).…”
Section: Novel Strategies For Remodulating the Cns Immune Responsementioning
confidence: 99%
“…Treg deficiency has been associated with increased disease progression in Alzheimer's disease, ALS, stroke, traumatic brain injury, and multiple sclerosis [4] . These reports and our works suggest that controlling neuroinflammation via Treg induction or enhancement may be a promising therapeutic avenue for the clinic [ 13 , 49 , 50 ]. Here, we show that sargramostim treatment induces Tregs and restores Treg function via increased demethylation of FOXP3 TSDR and enhanced expression of biomarkers necessary to maintain a suppressive phenotype.…”
Section: Discussionmentioning
confidence: 93%